Quantitative multiphoton microscopy of murine urinary bladder morphology during in situ uniaxial loading - Hornsby, J; Daly, D; Grundy, D; Cheng, F; Robertson, A; Watton, P; Thompson, M (Elsevier, 2017)
Urodynamic tests are the gold standard for the diagnosis of bladder dysfunction, and the mechanical compliance of the bladder is an important parameter in these tests. The bladder wall has a layered structure, differentially affected by pathology, so knowledge of the contribution and role of these layers and their constituents to overall bladder compliance will enhance interpretation of these clinical tests. In this study we document the functional morphology of the detrusor and lamina propria of the murine bladder wall using a custom in-situ tensile loading system under multiphoton microscopy (MPM) observation in unloaded state and under incremental uniaxial stretch. Features in the stress-stretch curves of bladder samples were then directly related to corresponding MPM images. Collagen organisation across wall depth was quantified using image analysis techniques. The hypothesis that the lamina propria deformed at low strain by unfolding of the rugae and rearranging collagen fibrils was confirmed. A novel ‘pocket’ feature in the detrusor was observed along with extensive rearrangement of fibrils in two families at different depths, providing higher stiffness at high stretches in the detrusor. The very different deformations of detrusor and lamina propria were accommodated by the highly coiled structure of collagen in the lamina propria. Imaging and mechanical studies presented here allow gross mechanical response to be attributed to specific components of the bladder wall and further, may be used to investigate the impact of microstructural changes due to pathology or aging, and how they impair tissue functionality.